2017
DOI: 10.1136/oemed-2016-103806
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhalation challenge: the relationship between response, clinical variables and lung function

Abstract: The scale of the response to SIC is influenced mainly by the degree of bronchial hyper-responsiveness, regardless of whether the causative agent is HMW or LMW, or whether the response is early or late.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Most studies have been with IgE-mediated reactions in which pre-challenge nonspecific reactivity is greater in dual than immediate reactors, and the magnitude of the immediate reaction is a determinant of the subsequent late reaction [19]. A population similar to ours from Barcelona showed that workers exposed to high molecular weight agents had increased SIC reactions compared to workers exposed to low molecular weight agents, and that bronchial responsiveness pre-SIC was the major determinant of the dose needed to elicit a reaction [20]. In our study with predominantly low molecular weight agents (and only two out of 53 with IgE antibodies to high molecular weight antigens), we found that larger immediate reactions did not predispose to dual reactions; all responses were allowed to resolve spontaneously without extra treatment, removing rescue treatment during SIC as a confounding factor.…”
Section: Discussionsupporting
confidence: 52%
“…Most studies have been with IgE-mediated reactions in which pre-challenge nonspecific reactivity is greater in dual than immediate reactors, and the magnitude of the immediate reaction is a determinant of the subsequent late reaction [19]. A population similar to ours from Barcelona showed that workers exposed to high molecular weight agents had increased SIC reactions compared to workers exposed to low molecular weight agents, and that bronchial responsiveness pre-SIC was the major determinant of the dose needed to elicit a reaction [20]. In our study with predominantly low molecular weight agents (and only two out of 53 with IgE antibodies to high molecular weight antigens), we found that larger immediate reactions did not predispose to dual reactions; all responses were allowed to resolve spontaneously without extra treatment, removing rescue treatment during SIC as a confounding factor.…”
Section: Discussionsupporting
confidence: 52%
“…38,39 The authors argue that DMHS is primarily a mycotoxicosis. Evaluation of the SIC test [40][41][42][43] shows that it lacks safety considerations and a careful assessment by independent clinicians of medical ethics, and may cause possible long-term adverse effects and even iatrogenic damage. The future directions for diagnosing and treating HP with an incidence of 0.3-0.9 per 100,000, irrespective of its cause, were highlighted by Vasakova et al 44 Based on the presented arguments, the authors challenge current practices related to the interpretation of occupational DMHS.…”
Section: Discussionmentioning
confidence: 99%